“Is it mixing?”: experiences in Early Childhood Education in Horizonte-CE using liquids - Alves, Maria Marly (2021)
This report portrays an experience that sought to contemplate the assumptions for pedagogical practices present in the Reference Curriculum Document of Ceará (2019), which is in line with the Common National Curriculum Base (2017) and the National Curriculum Guidelines for Early Childhood Education (2009), where it envisioned to guarantee practices that enable diversified and good quality experiences for children, guaranteeing genuine learning, fostering welcoming experiences in which it articulates the cultural, physical and social repertoire. The experience took place in infant classes III, morning shift, in a child education center in the city of Horizonte, in the period of August 2020, in a context of remote education. For this, we used the qualitative method through an experience report, where children explored different liquids, discharging discovery processes, child protagonism and authorial pleasure.